Impact of End-SARS on Academic Performance of Students of Political Science Education in Adekunle Ajasin University, Akungba-Akoko, Ondo State, Nigeria - Olowo, Oluwatoyin Oluwasegun; Adenigba, Idowu Eunice (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The End-SARS protest, which erupted across Nigeria in October 2020, marked a significant moment in the country’s contemporary civic and political history. Sparked by public outrage against police brutality—particularly by the Special Anti-Robbery Squad (SARS)—the movement rapidly expanded into a national call for systemic reform. This study investigates the impact of the End-SARS protest on academic performance, youth engagement, and economic stability, with a focus on students of Adekunle Ajasin University, Akungba-Akoko, Ondo State. Adopting a descriptive survey design, data were collected from 200 students selected through a multistage sampling technique across five faculties. A structured questionnaire was used to gather responses, which were analysed using frequency counts and simple percentages. Findings reveal that the protest significantly disrupted students’ academic activities, reduced study time, and contributed to delays in the academic calendar. Many students reported cognitive and emotional distress linked to the unrest. Beyond academics, the protest influenced youth engagement by fostering a stronger sense of political awareness and collective identity. Economically, students observed substantial losses among small and medium enterprises, reduced consumer spending, and business closures, especially in protest-affected areas. The study concludes that while the End-SARS protest served as a powerful expression of youth frustration and demand for justice, it also had unintended consequences for students’ academic progression and economic well-being. The research highlights the need for institutions and policymakers to develop crisis-responsive strategies that safeguard educational continuity and support youth resilience during periods of social upheaval.